Boronate-Based Fluorescent Probes as a Prominent Tool for H2O2 Sensing and Recognition - Wang, Ling; Hou, Xuben; Fang, Hao; Yang, Xinying (Current Medicinal Chemistry, 2022)
Given the crucial association of hydrogen peroxide with a wide range of human diseases, this compound has currently earned the reputation of being a popular biomolecular target. Although various analytical methods have attracted our attention, fluorescent probes have been used as prominent tools to determine H2O2 to reflect the physiological and pathological conditions of biological systems. The sensitive responsive part of these probes is the boronate ester and boronic acid groups, which are important reporters for H2O2 recognition. In this review, we summarize boronate ester/boronic acid group-based fluorescent probes for H2O2 reported from 2012 to 2020, and we have generally classified the fluorophores into six categories to exhaustively elaborate the design strategy and comprehensive systematic performance. We hope that this review will inspire the exploration of new fluorescent probes based on boronate ester/boronic acid groups for the detection of H2O2 and other relevant analytes.
Keywords: pathology